Empowering Blog as an Interesting Media for Learning English in Sma Wijaya Putra Surabaya - Syaiful Azmi; Yulis Setyowati; Angga Nur Viandi; Adam Mulyana Syahrudin (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2016)
The progress of technology in communication and information is growing more rapidly, as well as the utilization. This progress has spawned various types of activities which is based on the Internet network, such as e-government, e-commerce, e-learning and more. One obvious example of the development of information and communication technology in education is the implementation of e-learning. This proves that the utilization of information and communication technology today has become a necessity in a learning process in schools, especially for learning English. Social Media is an online media, with users able to easily participate, share and create contents include blogs, social networks, wikis, forums and virtual worlds. One social media which is suitable to be used as a medium of learning English is Blog. Blog is a web based application that resembles the form of writings (published as a post) on a common web.With the facilities provided by blog, there are some benefits that can be obtained, namely: the first benefit, using blog as a learning center. The second benefit, as the source to search references from internet sites that match to the material taught in the class, or to find other websites that are useful to expand the global knowledge of the students. And the third benefit is that blog can be used as a place to share opinions between student and student or students and teachers. The step is to make a Blogger community between classes.